A prosa de ficção francesa nos periódicos Diário de Pernambuco, O Liberal Pernambucano e Jornal do Recife (1850-1870): Joseph Méry e o público leitor - Santos, Reginaldo Clecio dos (2021)
This work aims reconstitute the modes of circulation of fiction prose in periodical newspapers of Recife, capital of the province of Pernambuco, between 1850 and 1870. In this sense, the survey of authors and authoress who were present in the sections destined to the fiction prose as well as in the columns with a variety comments about the cultural life of the province of the newspaper Diário de Pernambuco, Jornal do Recife and O Liberal Pernambucano. In parallel to this survey, it was done a bibliographic research that aimed to reconstruct the first steps of the history of typography, of the periodical press, as such as reconstruct fragments of memory of subjects and institutions directly and indirectly involved in the circulation of written culture in Pernambuco in the 19th century (CARVALHO, 1906; FREYRE, 1979; MELO, 1856, 1858; NASCIMENTO, 1966, 1968). To analyze the data collected in the periodicals from Recife, were utilized presupposed of Cultural History, especially the notions related to the practices and ways of circulation of printed materials in certain communities of readers, as well as the representations built by these communities from appropriations and specific representations (ABREU, 2003a, 2003b; BARBOSA, 2007; CHARTIER, 1999, 2012; MEYER, 1996, 1998). Thus, the survey undertaken demonstrated a majority presence, almost exclusive, of fiction prose produced in France, that circulated in Paris through periodical publications such as the Revue de Paris, Revue des Deux Mondes and the daily newspaper La Presse. From the analysis, it becomes possible to affirm that the prose of fiction, mostly from French periodicals, in circulation in periodical newspaper from Recife in the middle of the 19th century, shows evidence of criteria for the selection of fictional texts by editors and others involved in the translation and placement process, closely related to taste and the imaginary of at least part of the reading public in Pernambuco.